Computer Analysis of the Effects of Time and Gas Atmosphere of the Chemical Activation on the Development of the Porous Structure of Activated Carbons Derived from Oil Palm Shell - Mirosław Kwiatkowski (Energies, 2021)
The results of the advanced computer analysis of the influence of time and gas atmosphere of the chemical activation process on the microporous structure formation of activated carbons prepared from oil palm shell via microwave irradiation and activation, using potassium hydroxide as an activation agent, are presented in this paper. The quenched solid density functional theory (QSDFT) and the new numerical clustering-based adsorption analysis (LBET) methods were used especially in the analysis of the microporous structure of the activated carbons, taking into account the surface heterogeneity, and the results obtained were confronted with the simple results achieved earlier using Brunauer–Emmett–Teller (BET) and T-plot methods. On the basis of the computer analysis carried out and taking into account the results obtained, it has been shown that the material with the best adsorption properties and suitable for practical industrial applications is activated carbon obtained in a gaseous nitrogen atmosphere at an activation time of 30 min. Moreover, the value of the heterogeneity parameter indicates that the surface area of this activated carbon is homogeneous, which is of particular importance in the practical application. The paper emphasizes that an erroneous approach to the interpretation of analytical results based on gas adsorption isotherms, which consists in basing conclusions only on the values of a single parameter such as specific surface area or micropore volume, should be avoided. Therefore, it is recommended to use in the analysis of measurement data, several methods of porous structure analysis, including methods considering the heterogeneity of the surface, and when interpreting the results one should also take into account the adsorption process for which the analyzed materials are dedicated.